Global Economic Governance : IMF Quota Reform - Virmani, Arvind (Washington, D.C. : International Monetary Fund, 2011)
The paper examines the principles on which a reform of a Quota based global economic institution like the IMF must be based, taking account of both the relative economic power of countries and the need for voice and representation of the poor countries. These principles are then used in the context of the global economic realities of the 21st century to examine the suitability of different variables in the IMF.s Quota formula. Based on this analysis a simple transparent formula is suggested, which will help increase the credibility and legitimacy of the IMF as a global macroeconomic and financial institution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet